Design of a dual-input cross-connected charge pump utilizing scavenged energy - Kei Eguchi; Yutaka Kozono; Takaaki Ishibashi; Farzin Asadi (Energy Reports, 2020)
This paper presents a novel dual-input cross-connected charge pump utilizing scavenged energy. The proposed converter has two input sources: a battery input and a scavenged energy input. Unlike existing charge pumps, the proposed converter alleviates the energy consumed in a battery source by utilizing the scavenged energy. Therefore, the proposed converter can extend the lifetime of a battery source. Furthermore, the cross-connected structure offers not only higher voltage gain but also faster response speed than existing charge pumps. Through theoretical analysis and simulation program with integrated circuit emphasis (SPICE) simulation, the proposed converter demonstrates high power efficiency and high output voltage, where the proposed converter is compared with series-parallel converter, traditional charge pump, and Fibonacci converter. Concretely, about 90% power efficiency can be achieved by the proposed converter when the output power is 15~μW, and the settling time is less than 19~μS when the output load is 500kΩ. Furthermore, the feasibility of the proposed converter is confirmed by breadboard experiments, where the experimental circuit is built with commercially available ICs.
Keywords: 330; Charge pump; Cross-connected structure; Dual inputs; Energy harvesting; Inductor-less converters